Heart rate variability in people with visual disability: Study Protocol - Moreno, Renaldo D.; Abreu, Luiz C.; Morais, Mauro J D; Oliveira, Fabiano S.; Bezerra, Italla M P; Valenti, Vitor E. [UNESP]; Sato, Monica A. (Wolters Kluwer, 2019)
INTRODUCTION: People with visual impairment (VI) have loss of vision that causes impact on their daily living activities. Synonymous of VI are blindness, low vision, subnormal vision, visual incapacity, although there are peculiarities among them. The autonomic nervous system (ANS) provides the body with dynamic adaptation, moment by moment, according to changes in the internal and/or external body environment. As VI is an adverse condition, it is expected to be associated with changes in systemic autonomic activity, such as heart rate (HR) variability. OBJECTIVE: To analyze the blindness stress by monitoring the activity of the ANS in the heart in subjects submitted acutely to low vision and also in subjects with chronic visual deficiency. METHOD: This is a randomized trial experimental study. In this clinical trial, initially, patients will undergo an ophthalmologic medical evaluation, along with monitoring of HR and systolic blood pressure /diastolic blood pressure. Volunteers with normal vision (Group i); and people with VI (Group ii) will be evaluated, all of them inhabitants of Rio Branco City, capital of Acre State, Brazilian Amazon. The intervention will consist of simulating blindness by sealing both eyes of each participant with good eyesight, using a sleep mask and allowing maximum occlusion for 45 minutes, split into 3 periods of 15 minutes each. Still blindfolded, participants will be requested to perform different tasks as walking, serve themselves water and/or cookies, and engaging in playful-pedagogical activity. Identical procedure will be done with the group with VI. The HR will be recorded by the Polar RS800 HR monitor. All findings with a value of P < .05 will be considered statistically significant. As a risk measure the odds ratio will be calculated, adjusted, and not adjusted with their respective 95% confidence intervals. The odds ratio = 1 of lowest risk for the outcome of interest will be considered as the base category for each independent variable. ETHICS AND DISSEMINATION: This study will be carried out in accordance with the guidelines that regulate human research in Resolution No. 466/12 of the National Health Council. We obtained the approval of the Research Ethics Committee of the ABC Medical School/Faculdade de Medicina do ABC, with CAAE: 73945017.0.0000.0082, and Opinion No. 2,275,101. All individuals who agreed to participate in the study will sign the free and informed consent form (FICF). The FICF is also available in audio and Braille versions. The results will be disseminated through peer-reviewed journal articles and conferences. This study is registered in the Brazilian Registry of Clinical Trials under the number RBR-9sm9dp.